2022
DOI: 10.1007/s44202-022-00024-8
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol among young people in Iraq: a systematic scoping review

Abstract: Introduction Young people in Iraq are exposed to conflict and trauma, and to alcohol references in uncensored international TV and media. Previous regional reviews indicate that alcohol is the least studied substance in Arab countries and no data on young people in Iraq were identified. Accordingly, we re-examined the scope of available literature on alcohol and Iraqi young people, including in studies where alcohol was not the primary focus. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This study explored the health behaviors, knowledge, screening, and attitudes toward colorectal cancer among Iraqi people in Sulaymaniyah/Iraq and found that while more than half were smokers, the minority of participants had healthy behaviors like low rate of alcohol and fatty foods consumption and had high a low‐fiber diet. As alcohol is officially banned due to religious and cultural factors, Iraq has one of the low rates of drinking compared to non‐Muslim countries (Al Ansari et al., 2022), perhaps, prohibition and culture may have a factor in the low use of alcohol. On the contrary, more than half of the participants were smokers.…”
Section: Discussionmentioning
confidence: 99%
“…This study explored the health behaviors, knowledge, screening, and attitudes toward colorectal cancer among Iraqi people in Sulaymaniyah/Iraq and found that while more than half were smokers, the minority of participants had healthy behaviors like low rate of alcohol and fatty foods consumption and had high a low‐fiber diet. As alcohol is officially banned due to religious and cultural factors, Iraq has one of the low rates of drinking compared to non‐Muslim countries (Al Ansari et al., 2022), perhaps, prohibition and culture may have a factor in the low use of alcohol. On the contrary, more than half of the participants were smokers.…”
Section: Discussionmentioning
confidence: 99%
“…This study explored the health behaviors, knowledge, screening, and attitudes toward colorectal cancer among Iraqi people in Sulaymaniyah/ Iraq and found that while more than half were smokers, the minority of participants had healthy behaviors like low rate of alcohol and fatty foods consumption and had high a low-ber diet. As alcohol is o cially banned due to religious and cultural factors, Iraq has one of the low rates of drinking compared to non-Muslim countries [25], perhaps, prohibition and culture may have a factor in the low use of alcohol. On the contrary, more than half of the participants were smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying alcohol use, attitudes, and perceived motives for drinking among students allows for an assessment of their vulnerability. We were only able to identify two studies in local journals that assessed attitudes toward 'addiction' in general and medical samples (Al-Hasnawi, 2006;Al-Hasnawi, Al-Hemiary, & Lafta, 2007;Al Ansari et al, 2022). To our knowledge, there is currently no literature about attitudes to alcohol consumption and alcohol policy in Iraq among Iraqi university students.…”
Section: Alcohol Consumption Among University Students In Iraqmentioning
confidence: 99%
“…Despite the relatively low prevalence of alcohol use in the general population, risky drinking patterns are common among drinkers (Al Ansari, Dawson, & Conigrave, 2022). For example, the SSAI indicates that, on average, current drinkers consume more than six drinks per day on 10.5 days a month.…”
Section: Introductionmentioning
confidence: 99%